Impact of COVID-19 on the heart: Insight and current evidence based knowledge among Physicians - Shaha, Kunal Bikram; Shah, Prashant Kumar (Nepal Medical College Journal, 2022)
COVID 19 and its impact on the heart is a must to understand the disease in order to diagnose and manage the disease in time with a purpose of curbing down the fatality. This study aims to test and identify the gaps if any between the “Insight” and “current evidence based Knowledge” on the Impact of COVID-19 on the heart. A questionnaire based qualitative cross sectional descriptive study was conducted among Physicians all over Nepal directly or indirectly involved in COVID-19 management. Data was collected via google forms via email or viber/ whattsapp and laid in excel file. Proportion of response from each linked question in two sets containing 11 questions, was compared under the domain “Insight” versus “Current Evidenced based knowledge” having 5 various subtopics. One hundred doctors participated in the study. Overall positive difference of 19% was noted between insight and evidence based knowledge. The highest positive difference was noted regarding atrial fibrillation in COVID-19 (38%), rise in NT pro BNP and its prognosis in heart failure (35%), role of ACE-2 receptor in COVID-19 and acute lung injury (30%) and prevalence and type of arrhythmia in COVID-19 (25%) and lowest (-1%) in regard to preferred reperfusion therapy in STEMI in COVID-19. There were substantial gaps identified between insight and current evidence based knowledge which can be bridged by training, webinar, review article dissemination, peer clinical discussion at government and non-government level in all the states throughout the nation.